Human alterity - Salazar, Carles, author. Link
1 online resource (188 pages).
Keywords: Human Alterity: A Brief History of Anthropological Thought offers an introduction to the history of anthropological thought, encompassing eleven concise chapters that revolve around the concept of human alterity.Ever since the birth of our species, humans have wanted to understand people other than themselves. But what is an 'alter' human? Alter humans do not exist irrespective of the very concept of alterity that defines them as such. Readers find a history of what has made humanity opaque to itself: a history of the theories about human alterity produced by some humans. Chapters delve into various topics, including the discovery of America and the initial systematic theories regarding human alterity, the influences of rationalism and the Enlightenment, the impact of Romanticism, the trajectory of Social Evolutionism, the realm of Historicism, the tenets of Functionalism, explorations into the Culture and Personality school, examinations of Structuralism, analyses of political ideologies (such as Marxism, feminism, postcolonial studies, and postmodernism), and an exploration of current trends in cross-cultural studies.Human Alterity: A Brief History of Anthropological Thought will be of value to both new and advanced students of anthropology, sociology, cultural studies, social history, post-colonial studies and to anyone concerned with the belief, fantasy and reality of human diversity.